Arthroscopic Repair of a "Floating" Posterior Inferior Glenohumeral Ligament. Issue 4 (May 2022) - Greiner, Justin J.; Setliff, Joshua C.; Dworkin, Joshua D.; Lin, Albert
Background: Combined posterior glenoid labrum lesions with posterior humeral avulsion of the glenohumeral ligament, also known as the "floating" posterior inferior glenohumeral ligament (PIGL), occur infrequently. These combined lesions are frequently missed on magnetic resonance imaging in the workup of posterior shoulder instability. Correct identification of the "floating" PIGL lesion allows for appropriate preoperative planning and treatment to decrease the risk of recurrent posterior shoulder instability. Indications: A "floating" PIGL lesion is a cause of posterior shoulder instability and demonstrates increased translation when compared with isolated labral lesions. Surgical repair of an acute "floating" PIGL lesion with concomitant superior labral tear is described. Technique Description: The patient is placed in the lateral decubitus position. Standard posterior and anterior portals are created. In this case, a superior labral tear with anterior labral tear extension was also identified and repaired. The posterior labrum was repaired prior to the posterior humeral avulsion of the glenohumeral ligament (HAGL). The torn posterior labrum is mobilized and glenoid bony bed prepared. Short, 2.9-mm biocomposite knotless suture anchors loaded with suture tape are used for labral fixation. A 70° arthroscope is used to visualize the posterior HAGL from the anterior cannula and an additional posterior inferior portal established. The footprint of PIGL on the humerus is identified, debrided, and two 3.0-mm anchors loaded with suture placed. The sutures are passed through the capsule and PIGL and tied in a mattress pattern external to the capsule and ligament. The posterior portals are closed with nonabsorbable suture. Results: While few outcomes are described in the literature for the "floating" PIGL, the literature suggests good outcomes following surgical repair. Conclusion: The "floating" PIGL lesion is a rare cause of posterior shoulder instability. It is important to perform a thorough evaluation for concomitant pathology in patients with posterior shoulder instability as multiple structures can be injured. Arthroscopic repair of the posterior labrum and posterior humeral avulsion of the glenohumeral ligament can be performed to restore posterior stability to the shoulder in the setting of a "floating" PIGL. Graphical Abstract This is a visual representation of the abstract.